SISTEM INFORMASI PENJUALAN PADA CAFE RUANGTU7U BERBASIS WEB - Manda Manda; Emy L Tatuhey (ADISAM PUBLISHER, 2025)
This study aims to design and develop a web-based sales information system at Ruangtu7u Café in Jayapura, Papua. The problem faced by the café is the sales transaction process which is still done manually, such as recording orders and payments made in a tabulation book, so it is prone to recording errors, data manipulation, and difficulties in managing raw material stock. To overcome these problems, a sales information system was developed using the Waterfall method, which consists of the stages of needs analysis, system design using UML, implementation with the PHP programming language and MySQL/phpMyAdmin database, testing using the Blackbox method, and system implementation and maintenance. The results of this study indicate that the information system built is able to improve operational efficiency, transaction accuracy, and ease in preparing sales reports and stock management. In addition, the system has an interface that is easy to use by cashiers and management. This study contributes to overcoming manual transaction problems and supporting the digitalization of sales management in the small and medium enterprise (SME) sector, especially in the culinary field